Five new secondary metabolites from an endophytic fungus Phomopsis sp. SZSJ-7B - Chen, Yan; Wang, Huan; Ke, Xin; Sang, Zihuan; Kuang, Min; Peng, Weiwei; Tan, Jianbing; Zheng, Yuting; Zou, Zhenxing; Tan, Haibo (Frontiers in Plant Science, 2022)
Two previously undescribed lactones, phomolides A and B (1 and 2), and three new sesquiterpenoids, phomenes A–C (3–5), together with one known compound, colletotricholide A (6), were isolated from the endophytic fungus Phomopsis sp. SZSJ-7B. Their chemical structures, including the absolute configurations, were comprehensively established by extensive analyses of NMR, high-resolution electrospray ionization mass spectrometry, electronic circular dichroism powered by theoretical calculations, and X-ray diffractions. Moreover, the cytotoxic and antibacterial activities of compounds 1–6 were also evaluated, and the results demonstrated that compound 2 showed significant antibacterial effects towards methicillin-resistant Staphylococcus aureus and S. aureus strains with minimum inhibitory concentration as low as 6.25 μg/ml, which was comparable to that of the clinical drug vancomycin. Moreover, all compounds showed no cytotoxic activity.